Water distribution systems - Savic, Dragan, 1960-; Banyard, John K. (Thomas Telford, 2011)
Water industry professionals have to address, not only classic design and management problems but also, increasingly, environmental and sustainability requirements and concerns. Drawing together information that is currently scattered across several sources, this book is a concise update of modern practice and current developments.